Changing Organisational Culture: Leader’s Role In Changing Organisational Culture - Asral Kelvin Sahrain (Tadbir: Jurnal Manajemen Pendidikan Islam, 2018)
It has been generally agreed that in order to change the organisational culture it is best, first to change the people in the organisation. Since people are those who make the organisation works and lives. In this case the one who initiate change is the leader of that organisation. This paper will argue that leader is playing an important role in changing the culture of the organisation, and that there are some qualities of leaders needed to enable him/her to change the culture of the organisation.